1999
DOI: 10.1111/j.1365-2621.1999.tb15085.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Characteristics of Heat‐processed and Fresh Tomato Salsa Containing Honey

Abstract: Heat-processed and fresh salsa formulations were developed with different levels of honey (up to 10%), acid, and capsaicin. Descriptive sensory characteristics and consumer acceptability of the salsas were studied. Increasing levels of honey increased sweetness and crispness of both salsas. Higher levels of honey decreased oral heat intensity more than did lower levels. Consumers liked heat-processed salsa better than fresh and acceptability generally decreased with increasing honey content. However, about one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…According to Allison et al (1999) increased acidity suppressed the sweet perception in heat processed salsa. There was significant difference in sensory scores of the tomato salsa prepared with various levels of vinegar, sugar and cilantro.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Allison et al (1999) increased acidity suppressed the sweet perception in heat processed salsa. There was significant difference in sensory scores of the tomato salsa prepared with various levels of vinegar, sugar and cilantro.…”
Section: Resultsmentioning
confidence: 99%
“…Tomato salsa with steeped ingredients (onion, garlic, cilantro and capsicum) also showed good response from the panelists ( Table 2). Prepared recipe of tomato salsa was Standardized following the research done by Allison et al (1999) and Carlsen et al (1997). The data regarding the effect of different levels of acetic acid, sugar and cilantro concentrations on organoleptic quality of tomato salsa have been represented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, nonirritating aromas produced electrophysiological responses in the trigeminal nerve (Tucker 1971). Other research on a similar irritant, capsaicin, suggested that heat/burn could attenuate the perception of other tastes, such as sweetness in salsa (Allison et al. 1999) and sourness in chicken broth (Cowart 1987).…”
Section: Introductionmentioning
confidence: 99%